PENGARUH TERPAAN AKUN @MOTOMOBITV TERHADAP KEPUASAN FOLLOWERS DALAM MEMPEROLEH INFORMASI OTOMOTIF - Rina Astriani; Rani Puspita (Asosiasi Dosen Muda Indonesia, 2023)
This study aims to determine whether there is an effect of exposure to @motomobitv Instagram account on followers' satisfaction in obtaining automotive information using a quantitative approach method, and a positivistic paradigm. The theory used in this research is the theory of uses and gratification. The results of this study indicate that exposure to the Instagram account @motomobitv has an impact of 77.5% on follower satisfaction in obtaining automotive information, while the remaining 22.5% is influenced by other factors outside of this study. This study also has the results of Ho being rejected and Ha being accepted, which means that there is an influence on media exposure on follower satisfaction.